Visual complexity and the montado do matter: landscape pattern preferences of user groups in Alentejo, Portugal - Surová, Diana (2014)
Context The current paradigms for the sustainable development of forests and agriculture involve territorial organization of these activities as well as the multifunctionality of the related landscapes. Accordingly, the new management strategies need to take into account the suitability of the resulting landscapes to produce the goods and services expected by society. & Aims The aim of the study was to assess the preferred landscape patterns by different groups of users. In focus were the relations between the landscape metrics of preferred patterns and the individual characteristics of respondents.